CORRELATION BETWEEN MENTAL ACCOUNTING AND GROWTH OF SMALL BUSINESS ENTERPRISE IN NIGERIA - Abraham, Clement Sunny (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
Small-scale enterprises are an essential part of Nigeria's business sector. SMEs have been widely identified as the leading component of every society's economic growth and development. However, the sector has been fraught with numerous challenges in the Nigerian setting. Indeed, poor accounting management is one of the primary limitations linked to the failure and undergrowth in the small business sector. Thus, the present study aimed to investigate mental accounting as an accounting strategy that could enhance the growth of small-scale enterprises in Nigeria. The study employed a cross-sectional survey design. Eighty-seven (n=87) small and medium-scale operators randomly selected from the Enugu state business hub participated in the survey. The respondents completed a self-report questionnaire. A simple linear regression model was used for data analysis. It was found that mental accounting significantly predicted the growth of small-scale businesses in Nigeria. Implications and recommendations are discussed.